APPLICATION OF GROOMING AS A STANDARD FOR PROFESSIONALISM IN FOOD SERVICE AND BEVERAGE SERVICE AT KERATON AT THE PLAZA HOTEL JAKARTA (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Hospitality is one of the accommodations in the tourism sector, which provides facilities such as lodging, food and entertainment facilities. The hospitality industry is an industry that operates in the field of hospitality that is very influential on tourism in Indonesia. Grooming is one of the things or procedures that must be applied for everyone who works in the hospitality industry, in order to create a good and polite image in front of guests. The research will be conducted at the Keraton Hotel at The Plaza Jakarta, this Hotel was chosen as a place of research to find out whether the Keraton Hotel at The Plaza has implemented grooming in accordance with professional standards. This study uses a qualitative method with a descriptive approach, data collection techniques in this study using observation, documentation, interviews. So that a clear picture of the object under study can be obtained and conclusions can be drawn. Based on the results of the study showed that the application of Grooming as a Standard Professionalism in Food & Beverage Service at Keraton At The Plaza Hotel Jakarta is included in the good category and in accordance with the professional standards of a waiter. Keywords : Grooming, Waiter, Restaurant, Hotel